Rationalizing the effect of accelerated carbonation and accelerated ageing on transition zone of cellulose fibers in cement based composites - Tonoli, G. H.D.; Pizzol, V. D.; Urea, G.; Santos, S. F. [UNESP]; Mendes, L. M.; Santos, V.; Frias, M.; Savastano, H. (My University, 2015)
The objective of the present work is to show the effect of accelerated carbonation on the transition zone of cellulose fibers in cement based composites. Accelerated carbonation increased the content of calcium carbonate (CaCO3) polymorphs and consumed the calcium hydroxide (Ca(OH)2), and other less stable cement phases. The scanning electron microscopy (SEM) images showed that absence of S - and Al-rich needles around the cellulose fibers in the carbonated composites, and confirmed by the energy dispersive spectrometry (EDS) mapping. The CaCO3 formed from the carbonation reaction is precipitated in the pore structure of the matrix, decreasing diffusion of Si, S an AI during curing and secondary hydration, because act as a binder and refine the pore size distribution. The interface between the cellulose fibers and the cement matrix in the carbonated composites was improved, decreasing the typical transition zone around the cellulose fibers that prejudice the fiber-cement performance at long term. Additionally, the consequence of carbonation at early age is the volume stabilization, as indicated by the lower drying shrinkage. The use of this technology during the fiber-cement production consists of an interesting procedure to prematurely decrease the alkalinity of the cement matrix, which is potentially harmful to those reinforcing fibers that are vulnerable to the alkali attack. It also improves the microstructure of the material and is an initiative to CO2sequestration and partial replacement of petroleum-based fibers as is the case of cellulose pulps.
Keywords: A. Fibers; A. Hybrid; B. Fiber/matrix bond; E. cure; F. interface